Abstract 103: Acute Onset Rhythmic Tremor In Acute Frontal Cortical Infarction: A Case Report - JoBeth D. Bingham; Thomas Chelimsky; Shital Patel (Stroke: Vascular and Interventional Neurology)
Introduction Acute ischemic stroke varies in presentation, and it is crucial to quickly identify patients presenting with stroke for timely intervention. Secondary movement disorders occurring after a delayed period following ischemic stroke have been well‐documented, though rare. Holmes tremor specifically has been described as a delayed result of ischemic infarction involving subcortical structures such as mollaret triangle, thalamus, and basal ganglia. However, it is novel for frontal cortical infarcts to present with acute‐onset contralateral limb tremor, especially as an isolated symptom. Our case suggests a “secondary insult” involving the frontal cortex can disinhibit the motor pathway that leads to tremor in preexisting midbrain and thalamic lesions. We present a 67‐year‐old male with acute onset, constant, rhythmic tremor in the setting of acute ischemic frontal cortical infarction. Methods n/a, case report Results A 67‐year‐old male with medical history of pineal gland cyst status‐post shunt placement and hypertension who presented for evaluation of acute onset right upper extremity rhythmic tremor that started 24 hours prior. He did not have any associated weakness, numbness, vision changes, nausea, or vomiting. He had never had this tremor before. Neurologic examination was significant for a 4.0 Hz rhythmic resting tremor that was present throughout exam and was non‐distractible. This tremor remained consistent even with kinetic movements and postures. Electroencephalogram (EEG) was performed STAT during this tremor and was not based in seizure. Non‐contrast head computerized tomography (CT) was negative for any acute hemorrhage or intracranial pathology. CT angiogram head and neck showed left internal carotid artery (ICA) long segment tapered occlusion from the proximal cervical ICA to the distal petrous segment, likely dissection of undetermined chronicity. Magnetic resonance imaging (MRI) Brain with and without contrast was significant for acute punctate foci involving the precentral cortex of the left frontal lobe consistent with acute ischemic infarction. Encephalomalacia was also present involving the bilateral posterior thalami and left midbrain chronic ischemic infarctions. This suggests the tremor was caused by disinhibition of the motor pathway from the ischemic insult to the frontal cortex, as he had pre‐existing asymptomatic ischemic insult to the typical structures known to cause this tremor. He was outside of the Tenecteplase window and was given a load of Aspirin followed by aspirin 81 mg daily. He was trialed on propranolol for treatment of symptomatic tremor however this was discontinued before discharge as it was ineffective and patient preferred to hold off on other treatments. He is now awaiting outpatient Neurology follow up. Conclusion This case suggests that acute onset Holmes tremor can be the sole presenting sign in acute ischemic frontal cortical infarction. The pre‐existing asymptomatic infarctions in the midbrain and thalamus also support that a “second hit” located in the frontal cortex can disinhibit the motor pathway between the cortex and rubral tract. This is important as Holmes tremor is more commonly known to be from a mechanism of damage to the red nucleus or thalamic structures in a delayed manner, typically at least two weeks after stroke. This knowledge will help identify rare strokes in a timely manner.